Theorizing digital cultures - Bollmer, Grant (Sage, 2018)
The rapid development of digital technologies continues to have far reaching effects on our daily lives. This book explains how digital media--in providing the material and infrastructure for a host of practices and interactions--affect identities, bodies, social relations, artistic practices, and the environment.--Publisher's description.